1838 Ark. Rev. Stat. 280 - (:unkn) unknown (My University, 1838)
§ 13: Prohibited the concealed carry of any pistol, dirk, butcher, large knife, or sword-cane. Violators guilty of a misdemeanor, fined not less than twenty-five no more than one hundred dollars and shall be imprisoned not less than one nor more than six months.
Keywords: CARRY - CONCEALED